When you don't get what you want—and it's really hard: Exploring motivational contributions to exercise dropout. (July 2018) - Larson, Heather K.; McFadden, Kimberley; McHugh, Tara-Leigh F.; Berry, Tanya R.; Rodgers, Wendy M.
Abstract: Objectives: Dropout is a pervasive, yet understudied phenomenon in exercise behaviour. The purpose of this study was to explore the perceived individual, behavioural, and environmental influences experienced by 35–65-year-old adults who dropped out of a structured exercise programme. Design: This research took a qualitative description approach, with social-cognitive theory providing a guiding framework. Method: Semi-structured interviews were conducted with 17 participants (13 females and 4 males), with an average age of 49 years ( SD = 6.8). The interviews were audio-recorded, transcribed verbatim, and analysed using qualitative content analysis. Results: Findings are represented by four themes: (1) feeling good but disappointed, (2) scheduling issues, (3) trouble prioritizing exercise, and (4) exercising for/with someone else. Conclusions: These themes highlight the fragile nature of motivation for exercise. It seems the decision to continue exercising depends on a deliberate weighing of benefits against barriers. Unrealistic outcome expectations, low scheduling self-efficacy, and an unmet desire for social support and accountability can all influence this process in favour of drop out. Highlights: The regular and sustained incorporation of exercise into one's life is complex. New exercisers hold unrealistic outcome expectations and efficacy expectations. The weighing of exercise benefits against barriers seems to be a deliberate process. Motivation evolves over time and its components are not independent of each other.